Founding the year : Ovid's Fasti and the poetics of the Roman calendar - Pasco-Pranger, Molly. (Mnemosyne, Supplements, 2006)
This book considers the relationship between the Fasti , Ovid's long poem on the Roman calendar, and the calendar itself, conceived of as consisting both in the rites and commemorations it organizes and in its graphic representation. The Fasti treats the calendar, recently revised by Caesar and Augustus, as its most important cultural model and as a quasi-literary 'intertext': the poem simultaneously reshapes and is itself shaped by the calendar. The study includes chapters on Book 4 and the rites of April, on the addition of Julio-Claudian holidays to the calendar, and on the final two books of the poem as shaped by the renaming of the months Quintilis and Sextilis for Julius Caesar and Augustus.